Placental T2* as a measure of placental function across field strength from 0.55T to 3T - Hall, Megan; Verdera, Jordina Aviles; Cromb, Daniel; Silva, Sara Neves; Rutherford, Mary; Counsell, Serena J.; Hajnal, Joseph V.; Story, Lisa; Hutter, Jana (Scientific Reports, 2024)
Placental MRI is increasingly implemented in clinical obstetrics and research. Functional imaging, especially T2*, has been shown to vary across gestation and in pathology. Translation into the clinical arena has been slow because of time taken to mask the region of interest and owing to differences in T2* results depending on field strength. This paper contributes methodology to remove these barriers by utilising data from 0.55, 1.5 and 3T MRI to provide a fully automated segmentation tool; determining field strength dependency of placental assessment techniques; and deriving normal ranges for T2* by gestational age but independent of field strength. T2* datasets were acquired across field strengths. Automatic quantification including fully automatic masking was achieved and tested in 270 datasets across fields. Normal curves for quantitative placental mean T2*, volume and other derived measurements were obtained in 273 fetal MRI scans and z-scores calculated. The fully automatic segmentation achieved excellent quantification results (Dice scores of 0.807 at 3T, 0.796 at 1.5T and 0.815 at 0.55T.). Similar changes were seen between placental T2* and gestational age across all three field strengths (p < 0.05). Z-scores were generated. This study provides confidence in the translatability of T2* trends across field strengths in fetal imaging.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Fetal imaging; Placental MRI; T2* relaxometry